1999
DOI: 10.1002/(sici)1097-4636(199908)46:2<236::aid-jbm13>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

In vitro degradation of thin poly(DL-lactic-co-glycolic acid) films

Abstract: This study was designed to investigate the in vitro degradation of thin poly(DL-lactic-co-glycolic acid) (PLGA) films for applications in retinal pigment epithelium transplantation and guided tissue regeneration. PLGA films of copolymer ratios of 75:25 and 50:50 were manufactured with thickness levels of 10 microm (thin) and 100 microm (thick). Degradation of the films occurred during sample processing, and thin films with a higher surface area to volume ratio degraded faster. Sample weight loss, molecular wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
223
1
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 349 publications
(240 citation statements)
references
References 21 publications
13
223
1
3
Order By: Relevance
“…In Figure 10B, the homogenous, heterogeneous, and transition regimes predicted in the current study are compared to experimental observations of homogenous and heterogeneous diffusion in different sized samples (Chen et al, 1997;Grizzi et al, 1995;Lu et al, 1999;Park, 1995;Shirazi et al, 2014;Spenlehauer et al, 1989;Vey et al, 2008). Grizzi et al (1995) has proposed a range of 200-300 μm as a critical thickness above which the poly(D,L-lactic acid) polymers (plate, film, microsphere)(which have a similar chemical structure and degradation behaviour to PLGA) undergo heterogeneous degradation.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…In Figure 10B, the homogenous, heterogeneous, and transition regimes predicted in the current study are compared to experimental observations of homogenous and heterogeneous diffusion in different sized samples (Chen et al, 1997;Grizzi et al, 1995;Lu et al, 1999;Park, 1995;Shirazi et al, 2014;Spenlehauer et al, 1989;Vey et al, 2008). Grizzi et al (1995) has proposed a range of 200-300 μm as a critical thickness above which the poly(D,L-lactic acid) polymers (plate, film, microsphere)(which have a similar chemical structure and degradation behaviour to PLGA) undergo heterogeneous degradation.…”
Section: Discussionmentioning
confidence: 74%
“…Grizzi et al (1995) has proposed a range of 200-300 μm as a critical thickness above which the poly(D,L-lactic acid) polymers (plate, film, microsphere)(which have a similar chemical structure and degradation behaviour to PLGA) undergo heterogeneous degradation. The heterogeneous degradation of PLGA films with thicknesses of 300 μm, 250 μm, and 5-100 μm has been shown by Vey et al (2008), Shirazi et al (2014), and Lu et al (1999), respectively. Spenlehauer et al (1989) has showed that PLGA microspheres less than 200 μm in diameter undergo a homogeneous degradation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The lack of influence of the different Mn of PLGA or the lactic:glycolic acid ratio on protein release within a particular polymer group could be due to the degradation behavior of the polymers. Systematic studies of the degradation of the well-known PLGA with different lactic:glycolic acid ratios over 70 days or longer, show a faster degradation for a PLGA lactic:glycolic acid ratio of 50:50 and slower degradation for PLGA with a lactic:glycolic acid ratio of 75:25 (Lu et al, 2000(Lu et al, , 1999. However, the difference in release between these PLGAs is typically visible only after 10 to 20 days and is almost negligible for the first days.…”
Section: Ova Release From the Particlesmentioning
confidence: 99%